Antibacterial polyester-nylon composite fiber and preparation process thereof

By using a variety of fibers and bioactive peptides in polyester composite fibers, combined with the heteroformed cross-section design and coextrusion composite process, the problem of insufficient antibacterial performance of traditional polyester composite fibers is solved, and efficient antibacterial effect and environmental protection performance is achieved. in a variety of application fields.

CN119287556AInactive Publication Date: 2025-01-10WUHAN JIANGHUA FURNITURE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411698903.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional polyester broth composite fibers do not perform outstandingly in terms of antibacterial properties, and the preparation method is complex and costly, which is difficult to meet market demand. At the same time, some antibacterial fibers are highly irritating to human skin and do not meet the requirements of green and environmental protection.

Method used

An antibacterial polyester-based fiber, including polyester-based fiber, nylon-based fiber, bamboo fiber, soy protein fiber, polylactic acid fiber, bioactive peptide, silver ion fiber and cupric fiber, is designed through special cross-sectional design and nano-scale pores Structural and ion exchange technology, combined with coextrusion composite process and heat treatment, form multi-layered fibers.

Benefits of technology

It achieves excellent hygroscopicity, breathability and antibacterial properties of the fiber, reduces the impact on the environment, meets sustainable development requirements, and enhances the biocompatibility and skin care effects of the fiber.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287556A_ABST
    Figure CN119287556A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of composite fibers, in particular to an antibacterial polyester-nylon composite fiber and a preparation process thereof, overcomes the defects in the prior art, and comprises the following components: polyester-based fibers, nylon-based fibers, bamboo fibers, soybean protein fibers, polylactic acid fibers, bioactive peptides, silver ion fibers, cuprammonium silk fibers and Ek-silve polyester fibers. The composite fiber with multiple advantages of antibiosis, moisture absorption, air permeability, environmental protection, degradability and the like is obtained by proportioning a plurality of fiber raw materials and combining special structural design such as special-shaped sections and nanoscale holes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite fibers, and in particular to an antibacterial polyester-nylon composite fiber and a preparation process thereof. Background Art

[0002] With the advancement of science and technology and the improvement of people's quality of life, functional fiber materials are increasingly used in daily life. Among them, antibacterial fiber, as a material that can inhibit or kill microorganisms, has important application value in the fields of medical care, textiles, household goods, etc.

[0003] As a synthetic fiber that combines the advantages of polyester and nylon, polyester-nylon composite fiber has good physical and mechanical properties and chemical stability. However, the traditional polyester-nylon composite fiber does not perform well in antibacterial properties and is difficult to meet the growing market demand. Therefore, the development of a polyester-nylon composite fiber with excellent antibacterial properties has become a current research hotspot.

[0004] In the existing antibacterial fiber technology, although there are many methods used to improve the antibacterial properties of fibers, these methods often have some shortcomings. For example, some antibacterial fibers achieve antibacterial effects by adding antibacterial agents, but these antibacterial agents may gradually disappear during use, resulting in a decrease in antibacterial effects; in addition, the preparation methods of some antibacterial fibers are complex, costly, and difficult to mass produce; and some antibacterial fibers, although they have good antibacterial effects, are more irritating to human skin and do not meet the requirements of green environmental protection and human health.

[0005] Therefore, we proposed an antibacterial polyester-nylon composite fiber and its preparation process to solve the above problems. Summary of the invention

[0006] The purpose of the present invention is to solve the shortcomings of the prior art and to propose an antibacterial polyester-nylon composite fiber and its preparation process.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] An antibacterial polyester-nylon composite fiber comprises the following components in parts by weight: 30-40 parts of polyester-based fiber, 20-30 parts of nylon-based fiber, 5-10 parts of bamboo fiber, 5-10 parts of soybean protein fiber, 5-10 parts of polylactic acid fiber, 1-3 parts of bioactive peptide, 3-5 parts of silver ion fiber, 3-5 parts of cuprammonia silk fiber and 5-10 parts of Ek-silve polyester fiber.

[0009] As the preferred technical solution:

[0010] An antibacterial polyester-nylon composite fiber comprises the following components in parts by weight: 34 parts of polyester-based fiber, 23 parts of nylon-based fiber, 8 parts of bamboo fiber, 6 parts of soybean protein fiber, 7 parts of polylactic acid fiber, 2 parts of bioactive peptide, 4 parts of silver ion fiber, 4 parts of cuprammonia silk fiber and 7 parts of Ek-silve polyester fiber.

[0011] An antibacterial polyester-nylon composite fiber, wherein the fiber diameter of the polyester-based fiber is 10-20 microns; the fiber length of the nylon-based fiber is 38-51 millimeters; the average length of the bamboo fiber is 2.5-10 centimeters, and the porosity inside the bamboo fiber is between 10% and 20%; the fiber fineness of the polylactic acid fiber is 1.5-3.0 deniers; the molecular weight of the bioactive peptide is 500-2000 Daltons; the silver ion fiber contains 100-500 milligrams of silver per kilogram of fiber; the cuprammonia silk fiber contains 50-200 milligrams of copper per kilogram of fiber; and the fiber cross-section shape of the Ek-silve polyester fiber is circular or multi-lobed.

[0012] An antibacterial polyester-nylon composite fiber, wherein the polyester molecular chains and the nylon molecular chains in the polyester-based fiber and the nylon-based fiber are arranged linearly, and three rows are arranged parallel to each other; the antibacterial polyester-nylon composite fiber adopts a special-shaped cross-section design, including a cross shape, a star shape or a polygon, and / or a nanoscale hole structure is designed inside the antibacterial polyester-nylon composite fiber; the interaction between the polylactic acid fiber and the bioactive peptide is utilized to make them self-assemble on the fiber surface to form a nanoscale structure; and the ion exchange technology is utilized to exchange the ions in the silver ion fiber with the ions in the cuprammonia silk fiber, thereby adjusting the antibacterial property and electrical property of the fiber.

[0013] An antibacterial polyester-nylon composite fiber is designed with bamboo fiber and soybean protein fiber arranged alternately to form bamboo-node-shaped reinforcement nodes; the surface of the Ek-silve polyester fiber is designed with a micro-nano structure, including nano-protrusions and grooves.

[0014] The second aspect of the present invention provides a preparation process of an antibacterial polyester-nylon composite fiber, comprising the following steps:

[0015] S1: mixing polyester-based fibers and nylon-based fibers, melting the mixed fiber materials using a melt spinning machine, and passing the mixed fiber materials through a spinning hole to form primary fibers, and heat treating the primary fibers to obtain core fibers;

[0016] S2: bamboo fiber, soybean protein fiber, polylactic acid fiber, and Ek-silve polyester fiber are mixed and made into composite fibers using a blending spinning machine. In the outer layer of the composite fiber, the bioactive peptide is fixed on the surface of the composite fiber by a grafting modification method to obtain a shell fiber;

[0017] S3: crushing the silver ion fiber and the cuprammonium silk fiber respectively to obtain micro-nano-scale fiber fragments;

[0018] S4: The core fiber and the shell fiber are compounded together by co-extrusion technology, and micro-nano-scale fiber fragments are added to form a composite fiber with a multi-layer structure;

[0019] S5: heat treating the composite fiber to further improve its crystallinity and stability, and then stretching it to improve the orientation and mechanical properties of the fiber;

[0020] S6: Cut the stretched composite fiber, perform quality inspection on the cut fiber to ensure that there are no flaws and defects, and finally package it to obtain the finished antibacterial polyester-nylon composite fiber.

[0021] As the preferred technical solution:

[0022] In the above-mentioned process for preparing an antibacterial polyester-nylon composite fiber, in S1, a weak magnetic field is introduced during the heat treatment, and the guiding effect of the magnetic field is used to promote the regular arrangement of the chain segments inside the fiber.

[0023] In the preparation process of the antibacterial polyester-nylon composite fiber as described above, in S2, before the grafting modification, the outer surface of the composite fiber is roughened at the nanoscale to increase the surface area and create more grafting points.

[0024] The preparation process of the antibacterial polyester-nylon composite fiber as described above, wherein S4 specifically comprises:

[0025] S41: Before coextrusion, the core fiber and the shell fiber are preheated to ensure the fluidity and plasticity of the fiber material;

[0026] S42: start the co-extrusion compounding machine, set the temperature in the range of 200-250 degrees Celsius, and control the pressure in the range of 10-20 MPa to ensure that the fiber materials can be evenly mixed and will not be degraded due to high temperature;

[0027] S43: During the co-extrusion compounding process, the fiber material is vibrated by an ultrasonic vibration device;

[0028] S44: When the core fiber and the shell fiber are compounded in the co-extruder, the micro-nano fiber fragments that have been subjected to surface functionalization treatment are uniformly mixed into the composite fiber through the adding device, and the added amount is controlled to be 1-3% of the total amount of the composite fiber to ensure that the fiber fragments can be uniformly dispersed in the composite fiber without destroying the overall structure of the fiber;

[0029] S45: At the outlet of the co-extruder, a temperature control system and pressure regulation are used to ensure that the multi-layer structure of the composite fiber can be stably formed. A set of cooling devices is set at the outlet to quickly cool and shape the composite fiber;

[0030] S46: collecting the stably formed composite fibers on a winding device, and after the collection is completed, post-processing the composite fibers.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] Through structural design, the composite fiber exhibits excellent moisture absorption and breathability, allowing the product to remain dry and comfortable in humid or hot environments, improving the user experience.

[0033] The introduction of environmentally friendly materials such as polylactic acid makes the composite fiber have good biodegradability, reduces the impact on the environment, and meets the requirements of sustainable development. By designing the nano-scale pore structure, the moisture absorption and air permeability of the fiber can be further improved, and the fiber can also be given better thermal insulation performance.

[0034] The combination of bamboo fiber and soybean protein fiber not only improves the moisture absorption and air permeability of the fiber, but also enhances the affinity of the fiber to the skin through the biocompatibility of soybean protein, forming a fiber with skin care function. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a cross-sectional SEM photograph of the antibacterial polyester-nylon composite fiber of Example 4 of the present invention;

[0036] Figure 2 It is a data line chart of the embodiments and comparative examples of the present invention. DETAILED DESCRIPTION

[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. In the event of a conflict, the definitions in the specification shall prevail. "When mass, concentration, temperature, time, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood to specifically disclose all ranges formed by any pairing of any upper range limit or preferred value with any lower range limit or preferred value, regardless of whether the range is disclosed separately. For example, a range of 1-50 should be understood to include 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91 6, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, or 50, any number, combination of numbers, or subrange, and all decimal values ​​between the above integers, for example, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, and 1.9. With respect to subranges, "nested subranges" extending from any endpoint within the range are specifically contemplated. For example, nested subranges of the exemplary range 1-50 may include 1-10, 1-20, 1-30, and 1-40 in one direction, or 50-40, 50-30, 50-20, and 50-10 in the other direction."

[0038] The present invention is further explained below in conjunction with specific examples. The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are all commercially available unless otherwise specified.

[0039] An antibacterial polyester-nylon composite fiber comprises the following components in parts by weight: 30-40 parts of polyester-based fiber, 20-30 parts of nylon-based fiber, 5-10 parts of bamboo fiber, 5-10 parts of soybean protein fiber, 5-10 parts of polylactic acid fiber, 1-3 parts of bioactive peptide, 3-5 parts of silver ion fiber, 3-5 parts of cuprammonia silk fiber and 5-10 parts of Ek-silve polyester fiber.

[0040] Specifically, the fiber diameter of polyester-based fibers is 10-20 microns; the fiber length of nylon-based fibers is 38-51 millimeters; the average length of bamboo fibers is 2.5-10 centimeters, and the porosity inside bamboo fibers is between 10% and 20%; the fiber fineness of polylactic acid fibers is 1.5-3.0 deniers; the molecular weight of bioactive peptides is 500-2000 Daltons; in silver ion fibers, the silver content per kilogram of fiber is 100-500 milligrams; in cuprammonia silk fibers, the copper content per kilogram of fiber is 50-200 milligrams; the fiber cross-section shape of Ek-silve polyester fibers is round or multi-lobed.

[0041] It should be noted that in the polyester-based fibers and nylon-based fibers, the polyester molecular chains and the nylon molecular chains are arranged linearly, and the three rows are arranged parallel to each other; the antibacterial polyester-nylon composite fibers adopt a special-shaped cross-section design, including a cross, star or polygon, and / or a nano-scale pore structure is designed inside the antibacterial polyester-nylon composite fibers. These tiny holes can improve the air permeability and moisture absorption of the fibers, while allowing the antibacterial agent to penetrate into the fibers, thereby improving the durability of the antibacterial effect; utilizing the interaction between polylactic acid fibers and bioactive peptides, the polylactic acid fibers are self-assembled on the fiber surface to form a nano-scale structure, thereby improving the antibacterial effect and biocompatibility; utilizing ion exchange technology, the silver ion fibers are exchanged with the ions in the cuprammonia silk fibers, thereby adjusting the antibacterial and electrical properties of the fibers.

[0042] The following is a description of a specific embodiment of the antibacterial polyester-nylon composite fiber:

[0043] Example: Preparation of antibacterial polyester-nylon composite fiber

[0044] 1. Raw material preparation

[0045] Polyester-based fiber: Select polyester raw materials with moderate molecular weight and high crystallinity to ensure the linear arrangement of molecular chains.

[0046] Nylon-based fibers: Select nylon raw materials that are compatible with polyester-based fibers to promote the parallel setting of the molecular chains of the two.

[0047] 2. Fiber mixing and spinning

[0048] Mixing ratio: Polyester-based fibers and nylon-based fibers are mixed in a ratio of 70:30. This ratio helps to improve antibacterial properties while maintaining fiber strength.

[0049] Spinning process:

[0050] Melting temperature: set to 270°C to ensure complete melting of the fiber raw material.

[0051] Spinning speed: controlled at 3000 m / min to obtain uniform fiber diameter.

[0052] Cooling conditions: Gradual cooling is adopted to ensure the stability of the internal structure of the fiber.

[0053] 3. Special-shaped cross-section design and nanoscale pore structure

[0054] Special-shaped cross-section design: The cross-shaped cross-section is selected as the design of the antibacterial polyester-nylon composite fiber. This shape increases the surface area of ​​the fiber, which is conducive to the dispersion and penetration of the antibacterial agent.

[0055] Nanoscale pore structure:

[0056] Hole diameter: controlled within the range of 50-100 nanometers.

[0057] Hole distribution: Evenly distributed along the fiber axis to improve air permeability and moisture absorption.

[0058] Preparation method: Using phase separation technology, a porogen is introduced during the spinning process, and then the porogen is removed by heat treatment to form nanoscale pores.

[0059] 4. Self-assembly of polylactic acid fibers and bioactive peptides

[0060] Selection of PLA fiber: Choose PLA fiber with moderate molecular weight and high crystallinity.

[0061] Bioactive peptides: Select bioactive peptides that interact with polylactic acid fibers, such as peptide chains containing hydrophobic groups and hydrophilic groups.

[0062] Self-assembly conditions:

[0063] Temperature: controlled at 40 °C to facilitate the self-assembly process.

[0064] pH value: adjusted to 7.4 to simulate the physiological environment.

[0065] Time: 24 hours to ensure the stable formation of the self-assembled structure.

[0066] 5. Ion Exchange Technology

[0067] Preparation of silver ion fiber and cuprammonia fiber: Select fiber raw materials containing silver ions and copper ions respectively.

[0068] Ion exchange conditions:

[0069] Temperature: Set to 60°C to speed up ion exchange.

[0070] Concentration: Adjust the concentration of silver and copper ions to obtain the desired antimicrobial and electrical properties.

[0071] Time: Continue the exchange for 12 hours to ensure that the ion exchange is fully carried out.

[0072] 6. Post-processing and performance testing

[0073] Heat treatment: The antibacterial polyester-nylon composite fiber is heat treated to improve its crystallinity and stability. The heat treatment temperature is set at 140°C and the duration is 30 minutes.

[0074] Performance testing: The prepared antibacterial polyester-nylon composite fiber is tested for antibacterial properties, air permeability, moisture absorption and electrical properties to ensure that the product meets the design requirements.

[0075] It should be noted that the alternating arrangement of bamboo fiber and soybean protein fiber is designed to form bamboo-shaped reinforcement nodes; the micro-nano structure of the Ek-silve polyester fiber surface, including nano-protrusions and grooves, is designed to change the wettability and friction properties of the fiber surface and improve its binding ability with antibacterial agents.

[0076] The following is an example of how to achieve specific design requirements in antibacterial polyester-nylon composite fibers:

[0077] Example: Special design of antibacterial polyester-nylon composite fiber

[0078] 1. Bamboo fiber and soybean protein fiber are arranged alternately to form bamboo-shaped reinforcement nodes

[0079] Raw materials preparation:

[0080] Bamboo fiber: Choose bamboo fiber with uniform diameter and moderate strength.

[0081] Soy protein fiber: Choose soy protein fiber with good compatibility with bamboo fiber and moderate softness.

[0082] Alternating arrangement method:

[0083] Arrangement ratio: Bamboo fiber and soybean protein fiber are arranged alternately in a ratio of 1:1.

[0084] Arrangement: During the spinning process, the two fibers are alternately ejected through a precisely controlled spinneret to form a bamboo-shaped structure. The length of each bamboo-shaped reinforcement node is controlled between 1-2mm.

[0085] Enhanced node design:

[0086] Node spacing: The spacing of bamboo-type reinforcement nodes is set to 3-5mm to ensure the strength and flexibility of the fiber.

[0087] Node thickness: The thickness of the reinforced node is increased by about 20% compared to the conventional fiber part to enhance the reinforcement effect of the node.

[0088] 2. Ek-silve polyester fiber surface design micro-nano structure

[0089] Raw materials preparation:

[0090] Ek-silve Polyester Fiber: High quality Ek-silve polyester fiber is selected as the base material.

[0091] Micro-nano structure design:

[0092] Structural type: Design nano-protrusion and groove structure, the protrusion diameter is about 50-100nm, and the groove depth is about 20-50nm.

[0093] Distribution density: The distribution density of protrusions and grooves is 100-200 per square millimeter to ensure that the changes in the fiber surface can effectively affect its wettability and friction properties.

[0094] Preparation method:

[0095] Nano-imprint technology is used to create nano-protrusions and grooves on the surface of Ek-silve polyester fibers.

[0096] The designed micro-nano structure is achieved by precisely controlling the shape and depth of the imprint template, as well as the temperature, pressure and time during the imprinting process.

[0097] 3. Performance Testing and Verification

[0098] Surface morphology observation: Use scanning electron microscopy (SEM) to observe the micro-nano structure of the fiber surface to ensure that it meets the design requirements.

[0099] Wettability test: The wettability of the fiber surface is tested by a contact angle meter to verify the effect of the micro-nano structure on wettability.

[0100] Friction performance test: The friction coefficient of the fiber was tested using a friction tester to evaluate the changes in friction performance caused by the micro-nano structure.

[0101] Antimicrobial binding ability test: The antimicrobial agent is coated on the fiber surface, and the effect of the micro-nano structure on improving the antimicrobial binding ability is verified through comparative experiments.

[0102] Embodiment 1

[0103] An antibacterial polyester-nylon composite fiber comprises the following components in parts by weight: 30 parts of polyester-based fiber (Runye Geotech), 20 parts of nylon-based fiber, 5 parts of bamboo fiber (Zhejiang Yongguang Nonwoven Fabric Co., Ltd.), 5 parts of soybean protein fiber, 5 parts of polylactic acid fiber (Shenzhen Guanghua Weiye Co., Ltd.), 1 part of bioactive peptide (Xi'an Guohao Biotechnology Co., Ltd.), 3 parts of silver ion fiber (Jinan Yumo Science and Technology Trade Co., Ltd.), 3 parts of cuprammonia silk fiber (Asahi Kasei Shanghai), and 5 parts of Ek-silve polyester fiber.

[0104] The embodiment also proposes a preparation process of an antibacterial polyester-nylon composite fiber, comprising the following steps:

[0105] S1: The polyester-based fiber and the nylon-based fiber are mixed, and the mixed fiber material is melted by a melt spinning machine, and the melting temperature is controlled at 260°C, and the nascent fiber is formed through a spinning hole, and the diameter of the spinning hole is 0.1 mm. The nascent fiber is heat-treated at a temperature of 130°C for 30 minutes to enhance its crystallinity and mechanical strength. During the heat treatment, a weak magnetic field is introduced, and the strength of the weak magnetic field is controlled at 50mT. The guiding effect of the magnetic field is used to promote the regular arrangement of the internal chain segments of the fiber, thereby further improving the crystallinity and mechanical strength to obtain the core fiber;

[0106] S2: Bamboo fiber, soybean protein fiber, polylactic acid fiber, and Ek-silve polyester fiber are mixed and made into composite fibers using a blending spinning machine. The blending spinning temperature is controlled at 240°C. In the outer layer of the composite fiber, the bioactive peptide is fixed on the surface of the composite fiber by a grafting modification method. The grafting modification conditions are a reaction temperature of 60°C and a reaction time of 2 hours. Before the grafting modification, the outer surface of the composite fiber is roughened at the nanoscale by plasma etching. The treatment time is controlled at 10 minutes to increase the surface area and create more grafting points, thereby improving the attachment density and stability of the bioactive peptide to obtain a shell fiber.

[0107] S3: using a nano-grinder to ultrafine grind the silver ion fiber and the cuprammonium silk fiber, the grinding time is controlled within 30 minutes, to obtain micro-nano-scale fiber fragments, the size of the ground fiber fragments is 100 nanometers, and the micro-nano-scale fiber fragments are treated with plasma for surface functionalization;

[0108] S4: The core fiber and the shell fiber are compounded together by co-extrusion technology. The co-extrusion temperature is controlled at 220°C. Ultrasonic vibration is introduced during the co-extrusion process. The ultrasonic vibration frequency is 20kHz to enhance the interface bonding force between the layers of materials. At this time, micro-nano-scale fiber fragments are added to form a composite fiber with a multi-layer structure. During the compounding process, it is ensured that the layers are tightly bonded to avoid stratification.

[0109] S5: heat treating the composite fiber at a temperature of 120°C for 20 minutes to further improve its crystallinity and stability, and then stretching the fiber at a stretching ratio of 1.5 and a stretching speed of 10 m / min to improve the orientation and mechanical properties of the fiber;

[0110] S6: Cut the stretched composite fiber, perform quality inspection on the cut fiber to ensure that there are no flaws and defects, and finally package it to obtain the finished antibacterial polyester-nylon composite fiber.

[0111] Embodiment 2

[0112] An antibacterial polyester-nylon composite fiber comprises the following components in parts by weight: 32 parts of polyester-based fiber, 23 parts of nylon-based fiber, 6 parts of bamboo fiber, 7 parts of soybean protein fiber, 6 parts of polylactic acid fiber, 2 parts of bioactive peptide, 4 parts of silver ion fiber, 4 parts of cuprammonia silk fiber, and 7 parts of Ek-silve polyester fiber.

[0113] The embodiment also proposes a preparation process of an antibacterial polyester-nylon composite fiber, comprising the following steps:

[0114] S1: The polyester-based fiber and the nylon-based fiber are mixed, and the mixed fiber material is melted by a melt spinning machine, and the melting temperature is controlled at 265°C, and the nascent fiber is formed through a spinning hole, and the diameter of the spinning hole is 0.2 mm. The nascent fiber is heat-treated at a temperature of 134°C for 35 minutes to enhance its crystallinity and mechanical strength. During the heat treatment, a weak magnetic field is introduced, and the strength of the weak magnetic field is controlled at 60mT. The guiding effect of the magnetic field is used to promote the regular arrangement of the internal chain segments of the fiber, thereby further improving the crystallinity and mechanical strength to obtain the core fiber;

[0115] S2: Bamboo fiber, soybean protein fiber, polylactic acid fiber, and Ek-silve polyester fiber are mixed and made into composite fibers using a blending spinning machine. The blending spinning temperature is controlled at 250°C. In the outer layer of the composite fiber, the bioactive peptide is fixed on the surface of the composite fiber by a grafting modification method. The grafting modification conditions are a reaction temperature of 65°C and a reaction time of 3 hours. Before the grafting modification, the outer surface of the composite fiber is roughened at the nanoscale by plasma etching. The treatment time is controlled at 15 minutes to increase the surface area and create more grafting points, thereby improving the attachment density and stability of the bioactive peptide to obtain a shell fiber.

[0116] S3: using a nano-grinder to ultrafine grind the silver ion fiber and the cuprammonium silk fiber, the grinding time is controlled within 40 minutes, to obtain micro-nano-scale fiber fragments, the size of the fiber fragments after grinding is 200 nanometers, and plasma treatment is used to perform surface functionalization treatment on the micro-nano-scale fiber fragments;

[0117] S4: The core fiber and the shell fiber are compounded together by co-extrusion technology. The co-extrusion temperature is controlled at 230°C. Ultrasonic vibration is introduced during the co-extrusion process. The ultrasonic vibration frequency is 25kHz to enhance the interface bonding force between the layers of materials. At this time, micro-nano-scale fiber fragments are added to form a composite fiber with a multi-layer structure. During the compounding process, it is ensured that the layers are tightly bonded to avoid stratification.

[0118] S5: heat treating the composite fiber at a temperature of 130°C for 25 minutes to further improve its crystallinity and stability, and then stretching the fiber at a stretching ratio of 1.8 and a stretching speed of 15 m / min to improve the orientation and mechanical properties of the fiber;

[0119] S6: Cut the stretched composite fiber, perform quality inspection on the cut fiber to ensure that there are no flaws and defects, and finally package it to obtain the finished antibacterial polyester-nylon composite fiber.

[0120] Embodiment 3

[0121] An antibacterial polyester-nylon composite fiber comprises the following components in parts by weight: 37 parts of polyester-based fiber, 28 parts of nylon-based fiber, 9 parts of bamboo fiber, 8 parts of soybean protein fiber, 9 parts of polylactic acid fiber, 2 parts of bioactive peptide, 4 parts of silver ion fiber, 4 parts of cuprammonia silk fiber, and 7 parts of Ek-silve polyester fiber.

[0122] The embodiment also proposes a preparation process of an antibacterial polyester-nylon composite fiber, comprising the following steps:

[0123] S1: The polyester-based fiber and the nylon-based fiber are mixed, and the mixed fiber material is melted by a melt spinning machine, and the melting temperature is controlled at 270°C, and the nascent fiber is formed through a spinning hole, and the diameter of the spinning hole is 0.4 mm. The nascent fiber is heat-treated at a temperature of 140°C for 50 minutes to enhance its crystallinity and mechanical strength. During the heat treatment, a weak magnetic field is introduced, and the strength of the weak magnetic field is controlled at 80mT. The guiding effect of the magnetic field is used to promote the regular arrangement of the internal chain segments of the fiber, thereby further improving the crystallinity and mechanical strength to obtain the core fiber;

[0124] S2: Bamboo fiber, soybean protein fiber, polylactic acid fiber, and Ek-silve polyester fiber are mixed and made into composite fibers using a blending spinning machine. The blending spinning temperature is controlled at 250°C. In the outer layer of the composite fiber, the bioactive peptide is fixed on the surface of the composite fiber by a grafting modification method. The grafting modification conditions are a reaction temperature of 70°C and a reaction time of 3 hours. Before the grafting modification, the outer surface of the composite fiber is roughened at the nanoscale by plasma etching. The treatment time is controlled at 20 minutes to increase the surface area and create more grafting points, thereby improving the attachment density and stability of the bioactive peptide to obtain a shell fiber.

[0125] S3: using a nano-grinder to ultrafine grind the silver ion fiber and the cuprammonium silk fiber, the grinding time is controlled within 50 minutes, to obtain micro-nano-scale fiber fragments, the size of the ground fiber fragments is 350 nanometers, and the micro-nano-scale fiber fragments are treated with plasma for surface functionalization;

[0126] S4: The core fiber and the shell fiber are compounded together by co-extrusion technology. The co-extrusion temperature is controlled at 230°C. Ultrasonic vibration is introduced during the co-extrusion process. The ultrasonic vibration frequency is 30kHz to enhance the interface bonding force between the layers of materials. At this time, micro-nano-scale fiber fragments are added to form a composite fiber with a multi-layer structure. During the compounding process, it is ensured that the layers are tightly bonded to avoid stratification.

[0127] S5: The composite fiber is heat treated at a temperature of 130°C for 35 minutes to further improve its crystallinity and stability, and then stretched at a stretching ratio of 2.1 and a stretching speed of 22 m / min to improve the orientation and mechanical properties of the fiber;

[0128] S6: Cut the stretched composite fiber, perform quality inspection on the cut fiber to ensure that there are no flaws and defects, and finally package it to obtain the finished antibacterial polyester-nylon composite fiber.

[0129] Embodiment 4

[0130] An antibacterial polyester-nylon composite fiber comprises the following components in parts by weight: 40 parts of polyester-based fiber, 30 parts of nylon-based fiber, 10 parts of bamboo fiber, 10 parts of soybean protein fiber, 10 parts of polylactic acid fiber, 3 parts of bioactive peptide, 5 parts of silver ion fiber, 5 parts of cuprammonia silk fiber and 10 parts of Ek-silve polyester fiber.

[0131] The embodiment also proposes a preparation process of an antibacterial polyester-nylon composite fiber, comprising the following steps:

[0132] S1: The polyester-based fiber and the nylon-based fiber are mixed, and the mixed fiber material is melted by a melt spinning machine, and the melting temperature is controlled at 280°C, and the nascent fiber is formed through a spinning hole, and the diameter of the spinning hole is 0.5 mm. The nascent fiber is heat-treated at a temperature of 150°C for 60 minutes to enhance its crystallinity and mechanical strength. During the heat treatment, a weak magnetic field is introduced, and the strength of the weak magnetic field is controlled at 100mT. The guiding effect of the magnetic field is used to promote the regular arrangement of the internal chain segments of the fiber, thereby further improving the crystallinity and mechanical strength to obtain the core fiber;

[0133] S2: Bamboo fiber, soybean protein fiber, polylactic acid fiber, and Ek-silve polyester fiber are mixed and made into composite fibers using a blending spinning machine. The blending spinning temperature is controlled at 260°C. In the outer layer of the composite fiber, the bioactive peptide is fixed on the surface of the composite fiber by a grafting modification method. The grafting modification conditions are a reaction temperature of 80°C and a reaction time of 4 hours. Before the grafting modification, the outer surface of the composite fiber is roughened at the nanoscale by plasma etching. The treatment time is controlled at 30 minutes to increase the surface area and create more grafting points, thereby improving the attachment density and stability of the bioactive peptide to obtain a shell fiber.

[0134] S3: using a nano-grinder to ultrafine grind the silver ion fiber and the cuprammonium silk fiber, the grinding time is controlled within 60 minutes, to obtain micro-nano-scale fiber fragments, the size of the fiber fragments after grinding is 500 nanometers, and plasma treatment is used to perform surface functionalization treatment on the micro-nano-scale fiber fragments;

[0135] S4: The core fiber and the shell fiber are compounded together by co-extrusion technology. The co-extrusion temperature is controlled at 240°C. Ultrasonic vibration is introduced during the co-extrusion process. The ultrasonic vibration frequency is 40kHz to enhance the interface bonding force between the layers of materials. At this time, micro-nano-scale fiber fragments are added to form a composite fiber with a multi-layer structure. During the compounding process, it is ensured that the layers are tightly bonded to avoid stratification.

[0136] S5: heat treating the composite fiber at a temperature of 140°C for 40 minutes to further improve its crystallinity and stability, and then stretching the fiber at a stretching ratio of 3.0 and a stretching speed of 30 m / min to improve the orientation and mechanical properties of the fiber;

[0137] S6: Cut the stretched composite fiber, perform quality inspection on the cut fiber to ensure that there are no flaws and defects, and finally package it to obtain the finished antibacterial polyester-nylon composite fiber.

[0138] Comparative Example 1

[0139] An antibacterial polyester-nylon composite fiber and a preparation process thereof are basically the same as those in the fourth embodiment, except that: in step S4, specifically comprising:

[0140] S41: Before co-extrusion, the core fiber and the shell fiber need to be fully preheated at a temperature of 130 degrees Celsius for 12 minutes to ensure the fluidity and plasticity of the fiber material and prepare for the subsequent co-extrusion process.

[0141] S42: Start the co-extrusion machine and accurately set the temperature, pressure and speed parameters of the co-extruder according to the material properties of the core fiber and the shell fiber. It is recommended that the temperature be set at 230 degrees Celsius and the pressure be controlled at 14MPa to ensure that the fiber materials can be evenly mixed and will not be degraded due to high temperature;

[0142] S43: During the co-extrusion process, the fiber material is vibrated by an ultrasonic vibration device, the frequency of the ultrasonic wave is controlled at 30kHz, and the amplitude is adjusted to 8 microns, so as to effectively enhance the interface bonding force between the layers of materials and promote the fusion and bonding between different materials;

[0143] S44: When the core fiber and the shell fiber are compounded in the co-extruder, the micro-nano fiber fragments that have been subjected to surface functionalization treatment are uniformly mixed into the composite fiber through the adding device, and the added amount is controlled to be 2% of the total amount of the composite fiber to ensure that the fiber fragments can be uniformly dispersed in the composite fiber without destroying the overall structure of the fiber;

[0144] S45: At the outlet of the co-extruder, a precise temperature control system and pressure regulation are used to ensure that the multi-layer structure of the composite fiber can be stably formed. At this time, the layers of materials should be tightly combined without stratification. In order to further enhance the stability of the structure, a cooling device can be set at the outlet to quickly cool and shape the composite fiber.

[0145] S46: The stably formed composite fibers are collected on a winding device to prevent the fibers from being stretched or twisted during the collection process. After the collection is completed, the composite fibers are subjected to necessary post-processing, such as dust removal and static electricity removal, to ensure the cleanliness and performance of the fibers.

[0146] Comparative Example 1

[0147] An antibacterial polyester-nylon composite fiber and a preparation process thereof are basically the same as those in Example 4, except that the silver ion fiber and the cuprammonia silk fiber are removed.

[0148] Comparative Example 2

[0149] An antibacterial polyester-nylon composite fiber and a preparation process thereof are basically the same as those in Example 4, except that no bioactive peptide is added during the preparation process.

[0150] Comparative Example 3

[0151] An antibacterial polyester-nylon composite fiber and a preparation process thereof are basically the same as those in Example 4, except that the heat treatment in step S5 is omitted during the preparation process.

[0152] Comparative Example 4

[0153] An antibacterial polyester-nylon composite fiber and a preparation process thereof are basically the same as those of the fourth embodiment, except that a conventional circular cross-section is used instead of a special-shaped cross-section design.

[0154] The composite fibers prepared in the above-mentioned Examples 1 to 4, Comparative Example 1, and Comparative Examples 1 to 4 were tested:

[0155] Antibacterial performance test

[0156] National standard: GB / T 20944.1 / 2 / 3-2008 "Evaluation of antibacterial properties of textiles"

[0157] Detection method: Use the oscillation method or absorption method to inoculate a certain concentration of bacterial solution on the fiber sample. After a certain period of cultivation, the reduction rate of the number of bacteria is measured to evaluate the antibacterial effect.

[0158] Physical properties test

[0159] National Standard: GB / T 5455-2014 "Determination of vertical damage length, smoldering time and afterflame time of textile combustion performance"

[0160] Test method: Through the vertical combustion test, the damaged length, smoldering time and after-flame time of the fiber sample are measured to evaluate its combustion performance.

[0161] Safety performance test

[0162] National Standard: GB 18401-2010 "National Basic Safety Technical Specifications for Textile Products"

[0163] Testing methods: including testing of pH value, formaldehyde content, color fastness and other indicators to ensure the safety of fiber products.

[0164] The results are shown in Table 1:

[0165] Table 1

[0166]

[0167]

[0168] From Table 1 above, it can be directly obtained that the antibacterial effect of Control Example 1 is the best, slightly higher than that of other embodiments. This is due to the optimization of the co-extrusion compounding process in Control Example 1, including preheating treatment, precise parameter setting, ultrasonic vibration treatment, and rapid cooling and shaping, which are helpful for the dispersion and fixation of the antibacterial components, thereby improving the antibacterial rate.

[0169] The damaged length reflects the flame retardant performance of the fiber. The damaged length of Example 4 is the shortest, indicating that its flame retardant performance is relatively good. The damaged length of Comparative Example 1 is slightly longer than that of Example 4, but shorter than that of other examples, indicating that its flame retardant performance is also at a good level.

[0170] The pH values ​​of the embodiments and control examples were all within the normal range (6.6 to 6.9), indicating that different treatments during the preparation process had little effect on the pH value of the fiber.

[0171] The color fastness of Examples 1 to 4 is all 4-5, while the control example 1 reaches level 5. This shows that the control example 1 performs better in color retention because the optimized treatment in the co-extrusion composite process improves the color stability.

[0172] In summary, by comparing the data of Examples 1 to 4 and Control Example 1, we can find that Control Example 1 shows better performance in terms of antibacterial rate, damaged length and color fastness. This shows that the optimization of the co-extrusion composite process in Control Example 1 has a positive effect on improving fiber performance, and the performance of Examples 1 and 4 is also excellent.

[0173] Reference Figure 1-2 , in Example 4 and Comparative Example where other conditions are the same:

[0174] Antibacterial performance (Staphylococcus aureus inhibition rate)

[0175] Example 4: The antibacterial rate is 98.1%, showing excellent antibacterial performance.

[0176] Comparative Example 1: After removing the silver ion fiber and the copper ammonia silk fiber, the antibacterial rate dropped to 85%. This shows that the silver ion fiber and the copper ammonia silk fiber play an important role in the antibacterial properties of the composite fiber. Comparative Example 2: After not adding the bioactive peptide, the antibacterial rate further dropped to 75%. This shows that the bioactive peptide is also critical for enhancing the antibacterial properties. Comparative Example 3: After omitting the heat treatment in step S5, the antibacterial rate was 90%. Although it still shows a certain antibacterial effect, it is lower than Example 4, indicating that heat treatment is necessary to maintain or enhance the antibacterial properties. Comparative Example 4: After not adopting the special-shaped cross-section design, the antibacterial rate is 88%. This shows that the cross-sectional design of the fiber affects the antibacterial properties to a certain extent.

[0177] Physical properties (damage length)

[0178] Example 4: The damaged length is 43 mm, showing good flame retardancy.

[0179] Comparative Example 1: The damaged length increased to 55 mm, indicating that the flame retardancy decreased after the silver ion fiber and the cuprammonium silk fiber were removed. Comparative Example 2: The damaged length was 50 mm, which was still higher than Example 4, indicating that the absence of bioactive peptides also had an adverse effect on the flame retardancy. Comparative Example 3: The damaged length further increased to 60 mm, indicating that omitting the heat treatment step significantly reduced the flame retardancy. Comparative Example 4: The damaged length was 52 mm, indicating that the cross-section design also had a certain effect on the flame retardancy.

[0180] Safety performance (pH value)

[0181] The pH values ​​of all samples were between 6.6 and 7.1, which met the requirements of textile safety standards. This shows that the preparation process conditions had little effect on the pH value of the composite fibers and were all kept within a safe range.

[0182] Safety performance (color fastness)

[0183] Example 4: The color fastness is level 4-5, showing good color fastness.

[0184] Comparative Examples 1 to 4: The color fastness is mostly level 4 or slightly lower. This indicates that some changes in the preparation process (such as removing specific fibers, omitting the heat treatment step, etc.) have a certain impact on the color fastness, but the overall impact is not significant.

[0185] In summary, silver ion fiber and cuprammonium silk fiber are essential for improving the antibacterial properties of antibacterial polyester-nylon composite fibers. The addition of bioactive peptides also helps to enhance the antibacterial properties. The heat treatment in step S5 is necessary to maintain or improve the antibacterial properties and flame retardancy. The cross-sectional design of the fiber affects the antibacterial properties and flame retardancy to a certain extent. The pH values ​​of all samples meet the safety standards, while the color fastness is less affected by changes in the preparation process.

[0186] The present invention creates a composite fiber with a multi-layer structure and special physical properties by carefully selecting and proportioning a variety of fiber raw materials, including polyester-based fibers, nylon-based fibers, bamboo fibers, soybean protein fibers, polylactic acid fibers, bioactive peptides, silver ion fibers, cuprammonia silk fibers, and Ek-silve polyester fibers. In addition, by introducing innovative means such as special-shaped cross-section design, nanoscale pore structure, and micro-nano surface treatment, the antibacterial effect, hygroscopicity, air permeability, and other key properties of the fiber are further improved.

[0187] By integrating multiple antibacterial ingredients such as silver ion fiber, cuprammonium silk fiber and bioactive peptides, the composite fiber exhibits long-lasting and highly effective antibacterial ability, which is crucial in the fields of medical care, textiles and household products, helping to reduce the growth and spread of bacteria.

[0188] The design of bamboo fiber, soybean protein fiber and nano-scale pore structure significantly improves the moisture absorption and breathability of the fiber. This makes the fiber remain comfortable in hot or humid environments, especially suitable for sportswear, bedding, etc.

[0189] The introduction of polylactic acid fiber gives the composite fiber good biodegradability, which meets the current demand for environmentally friendly materials. This helps reduce the burden of waste on the environment and promotes sustainable development.

[0190] Through a carefully designed preparation process, including heat treatment, stretching, and ultrasonic vibration, the composite fiber exhibits high strength and good wear resistance. This extends the service life of the fiber and improves the durability of the product.

[0191] The biocompatibility of soy protein fiber enhances the affinity of fiber to the skin, providing users with additional skin care effects. This has significant advantages in the fields of sensitive skin care, baby products, etc.

[0192] The special-shaped cross-section and nanoscale structure design not only improves the performance of the fiber, but also provides more possibilities for its application in high-end textiles and functional materials.

[0193] In summary, this technology has successfully developed an antibacterial polyester-nylon composite fiber with multiple advantages through innovative component combination and structural design, which is expected to be widely used in multiple fields and promote technological progress in related industries.

[0194] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. An antibacterial polyester-nylon composite fiber, characterized in that: The invention comprises the following components in parts by weight: 30-40 parts of polyester-based fiber, 20-30 parts of nylon-based fiber, 5-10 parts of bamboo fiber, 5-10 parts of soybean protein fiber, 5-10 parts of polylactic acid fiber, 1-3 parts of bioactive peptide, 3-5 parts of silver ion fiber, 3-5 parts of cuprammonia silk fiber and 5-10 parts of Ek-silve polyester fiber.

2. The antibacterial polyester-nylon composite fiber according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 34 parts of polyester-based fiber, 23 parts of nylon-based fiber, 8 parts of bamboo fiber, 6 parts of soybean protein fiber, 7 parts of polylactic acid fiber, 2 parts of bioactive peptide, 4 parts of silver ion fiber, 4 parts of cuprammonia silk fiber and 7 parts of Ek-silve polyester fiber.

3. The antibacterial polyester-nylon composite fiber according to claim 1 or 2, characterized in that: The fiber diameter of the polyester-based fiber is 10-20 microns; The fiber length of the nylon-based fiber is 38-51 mm; The average length of the bamboo fiber is 2.5-10 cm, and the porosity inside the bamboo fiber is between 10% and 20%; The fiber fineness of the polylactic acid fiber is 1.5-3.0 denier; The molecular weight of the bioactive peptide is 500-2000 Daltons; The silver ion fiber contains 100-500 mg of silver per kilogram of fiber; The copper-ammonia silk fiber contains 50-200 mg of copper per kilogram of fiber; The Ek-silve polyester fiber has a cross-sectional shape of a circular or multi-lobal fiber.

4. The antibacterial polyester-nylon composite fiber according to claim 1 or 2, characterized in that: In the polyester-based fibers and nylon-based fibers, the polyester molecular chains and the nylon molecular chains are arranged linearly, and three rows are arranged parallel to each other; The antibacterial polyester-nylon composite fiber adopts a special-shaped cross-section design, including a cross shape, a star shape or a polygon shape, and / or a nano-scale hole structure is designed inside the antibacterial polyester-nylon composite fiber; The interaction between the polylactic acid fiber and the bioactive peptide is utilized to self-assemble on the fiber surface to form a nano-scale structure; By using ion exchange technology, the ions in the silver ion fiber and the cuprammonia silk fiber are exchanged, thereby adjusting the antibacterial and electrical properties of the fiber.

5. The antibacterial polyester-nylon composite fiber according to claim 1 or 2, characterized in that: Design the alternating arrangement of bamboo fiber and soybean protein fiber to form bamboo-shaped reinforcement nodes; The surface of the Ek-silve polyester fiber is designed with a micro-nano structure, including nano-protrusions and grooves.

6. A process for preparing the antibacterial polyester-nylon composite fiber according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1: mixing polyester-based fibers and nylon-based fibers, melting the mixed fiber materials using a melt spinning machine, and passing the mixed fiber materials through a spinning hole to form primary fibers, and heat treating the primary fibers to obtain core fibers; S2: bamboo fiber, soybean protein fiber, polylactic acid fiber, and Ek-silve polyester fiber are mixed and made into composite fibers using a blending spinning machine. In the outer layer of the composite fiber, the bioactive peptide is fixed on the surface of the composite fiber by a grafting modification method to obtain a shell fiber; S3: crushing the silver ion fiber and the cuprammonium silk fiber respectively to obtain micro-nano-scale fiber fragments; S4: The core fiber and the shell fiber are compounded together by co-extrusion technology, and micro-nano-scale fiber fragments are added to form a composite fiber with a multi-layer structure; S5: heat treating the composite fiber to further improve its crystallinity and stability, and then stretching it to improve the orientation and mechanical properties of the fiber; S6: Cut the stretched composite fiber, perform quality inspection on the cut fiber to ensure that there are no flaws and defects, and finally package it to obtain the finished antibacterial polyester-nylon composite fiber.

7. The process for preparing an antibacterial polyester-nylon composite fiber according to claim 6, characterized in that: In S1, a weak magnetic field is introduced during the heat treatment, and the guiding effect of the magnetic field is used to promote the regular arrangement of the chain segments inside the fiber.

8. The process for preparing an antibacterial polyester-nylon composite fiber according to claim 6, characterized in that: In S2, before the grafting modification, the outer surface of the composite fiber is roughened at the nanoscale to increase the surface area and create more grafting points.

9. The process for preparing an antibacterial polyester-nylon composite fiber according to claim 6, characterized in that: The S4 specifically includes: S41: Before coextrusion, the core fiber and the shell fiber are preheated to ensure the fluidity and plasticity of the fiber material; S42: start the co-extrusion compounding machine, set the temperature in the range of 200-250 degrees Celsius, and control the pressure in the range of 10-20 MPa to ensure that the fiber materials can be evenly mixed and will not be degraded due to high temperature; S43: During the co-extrusion compounding process, the fiber material is vibrated by an ultrasonic vibration device; S44: When the core fiber and the shell fiber are compounded in the co-extruder, the micro-nano fiber fragments that have been subjected to surface functionalization treatment are uniformly mixed into the composite fiber through the adding device, and the added amount is controlled to be 1-3% of the total amount of the composite fiber to ensure that the fiber fragments can be uniformly dispersed in the composite fiber without destroying the overall structure of the fiber; S45: At the outlet of the co-extruder, a temperature control system and pressure regulation are used to ensure that the multi-layer structure of the composite fiber can be stably formed. A set of cooling devices is set at the outlet to quickly cool and shape the composite fiber; S46: collecting the stably formed composite fibers on a winding device, and after the collection is completed, post-processing the composite fibers.